Work training and work discipline on employee productivity - Andini Damayanti; Esti Margiyanti Utami; Fitri Rahmawati (www.amertainstitute.com, 2025)
A good company or agency will manage human resources well. The company places human resources as the company's main asset and is very dependent on the human resources it has. It can be viewed from From an organizational standpoint, productivity represents a distinct concept that goes beyond mere attempts to improve the efficiency and outcomes both in quality and quantity of a series of activities. Rather, it should be understood within a broader economic context involving systemic processes and strategic goals. This study was conducted to examine the influence of job training on employee productivity and to evaluate the role of work discipline in enhancing productivity outcomes. The research population included all staff members of Perumda Air Minum Tirta Bumi Sentosa, located in Kebumen Regency. A census sampling technique (saturated sampling) was utilized, resulting in 102 valid respondents. Data were gathered through a structured questionnaire featuring Likert-scale items, all of which had undergone validity and reliability testing. To analyze the data, multiple linear regression analysis was applied as the core statistical method. The findings indicated that job training contributes positively to enhancing employee productivity, while work discipline.